พัฒนาการของสื่อประชาสังคมไทยบนอินเทอร์เน็ต - มนทกานติ์ ตปนียางกูร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To study the development of five civic information websites, that is, the website of the working group on civic media (http://www.prachachon.net), the website of the Prachatham news agency (http://www.newspnn.net), the website of the Silpakam Krachok-ngao group (http://www.bannok.com), the website of the Thaitopic dot com (http://www.thaitopic.com), and the website of the Thai NGO network (http://www.thaingo.org). The objectives of the research is to study the development of the websites, their format and presentation of content; to examine whether these websites have the characteristics of civic media and the role played by information and communication technologies (ICTs) in the development of these websites. The study uses content analysis and in-depth interview as major methods of data collection. The research finds that the five studied websites play a different role as civic media. While the website of the working group on civic media plays a key role in public provision of civic information, the remaining four websites (the website of the Prachatham news agency, the website of the Silpakam Krachok-ngao group, the website of the Thaitopic dot com, and and the website of the Thai NGO network) play these roles quite prominently: journalistic reporting, mobilization of resources for rural development, public education about civic matters, and center of civic networking or civic portal, in that respective order. The study also finds that although the Internet has many positive attributes for civic networking such as low cost, two-way communication, speed, borderlessness, and user anonymity, its rate of diffusion in Thailand is limited to only the middle-class population. Besides, the type of communication prevalent in webboards is also found to contain mostly irrational and emotional debates. Therefore, it could not lead to conclusive action or resolution for a problem, that would pave the way for a public sphere.